Thoughts on diagnosis and treatment of catheter - Related refractory upper urinary tract Bleeding:A case report - Chaohua Deng; Yuan Zhou; Guofu He; Jiongming Li; Guang Wang; Yu Zhang (Urology Case Reports)
We present an extremely rare case of refractory upper urinary tract bleeding related to a single ''J'' tube, unreported globally. A patient with high - grade invasive urothelial carcinoma had LRC + bilateral uretero - cutaneous ostomy, then bleeding unresponsive to transfusion and RAE. Recovery came after tube removal, with no hematuria in 2 - month follow - up.